Evaluación técnica, económica y ambiental de un bloque ecológico de chasqui y plástico PET en la construcción - Laborde Nupia, Grace Dayana (2025)
This research project addresses the current problem of plastic pollution, proposing its use in the production of ecological blocks, a sustainable alternative for the construction industry. Plastic waste is collected and combined with flint, sand, cement, and water to obtain the final product. The objective is to describe the physical, ecological, and economic properties of ecological blocks, comparing them with traditional blocks. Various tests were conducted on the environmental block to assess its strength, firmness, and absorption, yielding favorable and promising results. The methodology employed combines a qualitative and quantitative approach, utilizing exploratory, experimental, and descriptive data collection methods. The results indicate that the ecological block represents a feasible alternative for reducing plastic waste and, at the same time, strengthens the construction industry as a sustainable and economical solution.